SPATIAL PLANNING OF BENGAWAN SOLO RIVER WATERFRONT AREA TO STRENGTHEN BOJONEGORO CITY’S IDENTITY - Okita Sisy Tiara (Lakar: Jurnal Arsitektur, 2023)
The Bengawan Solo River passes through and is along the northern area of Bojonegoro City. So that the riverside area in the northern region of this district is generally used as an agricultural area because of its fertile soil. However, the area on the banks of the Bengawan Solo river which is in the center of the city, namely in the area adjacent to the center of government, squares, traditional markets, and the grand mosque, has not been properly planned out and tends to be neglected, giving rise to a slum impression. Whereas the development of livable waterfront areas in areas adjacent to major rivers or the sea (waterfront city), is very important to be realized for the benefit of Bojonegoro residents and the environment of the waterfront area itself. This neglected and slum waterfront area, even though it is in the city center, also creates other problems such as the loss of identity and characteristics of the city of Bojonegoro. This research aims to bridge the difference between empirical conditions in the field and ideal conditions in a riverside area, in order to improve the quality of the area in question. So the proposed design for the revitalization of the waterfront area will not only have broad benefits for residents and the environment, but will also improve the image of the rundown waterfront area into a beautiful and livable waterfront area, thus also helping to strengthen the identity of the city of Bojonegoro. By using qualitative methods and a rationalistic paradigm, as well as in-depth and comprehensive observation and analysis, the design recommendations from this research can be useful for the people of Bojonegoro and are in line with the Government's program.